2023
DOI: 10.1177/20584601231205159
|View full text |Cite
|
Sign up to set email alerts
|

Can virtual non-contrast imaging replace true non-contrast imaging in multiphase scanning of the neck region?

Zaid Al-Difaie,
Max HMC Scheepers,
Nicole D Bouvy
et al.

Abstract: Background Dual-energy computed tomography (DECT) is an advanced imaging method that enables reconstruction of virtual non-contrast (VNC) images from a contrast-enhanced acquisition. This has the potential to reduce radiation exposure by eliminating the need for a true non-contrast (TNC) phase. Purpose The purpose is to evaluate the feasibility of VNC images in the neck region. Materials and methods A total of 100 patients underwent a DECT scan as part of diagnostic workup of primary hyperparathyroidism. VNC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Additionally, several studies have shown that DECT-derived VNC reconstructions cannot totally substitute TNC images. In the imaging of the neck, a significant variation in the density of the thyroid tissue has been demonstrated between VNC reconstructions and TNC [ 16 ]. In the detection of kidney stones, the accuracy of DECT-derived VNC reconstructions was also limited by the surrounding iodine-enhanced contrast [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies have shown that DECT-derived VNC reconstructions cannot totally substitute TNC images. In the imaging of the neck, a significant variation in the density of the thyroid tissue has been demonstrated between VNC reconstructions and TNC [ 16 ]. In the detection of kidney stones, the accuracy of DECT-derived VNC reconstructions was also limited by the surrounding iodine-enhanced contrast [ 17 ].…”
Section: Introductionmentioning
confidence: 99%